Switching between eltrombopag and recombinant human thrombopoietin in patients with immune thrombocytopenia: an observational study. Issue 19 (5th October 2022) - Cai, Xuan; Fu, Haixia; Zhao, Xiangyu; Lu, Jin; Jiang, Qian; Chang, Yingjun; Huang, Xiaojun; Zhang, Xiaohui
Abstract : Background: Recombinant human thrombopoietin (rh-TPO) and eltrombopag are two distinct TPO receptor agonists (TPO-RAs) with different mechanisms. During the pandemic, when immunosuppressive medications are controversial, switching to another TPO-RA may be worth exploring in patients who do not benefit from their first TPO-RA. We investigated the outcomes of switching from rh-TPO to eltrombopag or vice versa in immune thrombocytopenia (ITP) patients. Methods: This prospective, open-label, observational investigation included 96 adult ITP patients who needed to switch between rh-TPO and eltrombopag between January 2020 and January 2021 at Peking University People's Hospital in China. The study evaluated response rates and platelet counts at different time points after the switch, bleeding events, time to response, duration of response, and adverse events. Results: At 6 weeks after switching, response was observed in 21/49 patients (43%) who switched for inefficacy and 34/47 patients (72%) who switched for non-efficacy-related issues. In the inefficacy group, 9/27 patients (33%) responded to eltrombopag, and 12/22 patients (55%) responded to rh-TPO. In the non-efficacy-related group, 21/26 (81%) and 13/21 (62%) patients in the eltrombopag and rh-TPO groups maintained their response rates at 6 weeks after switching, respectively. Response at 6 months was achieved in 24/49 patients (49%) switching for inefficacy and 37/47 patients (79%) switching for non-efficacy issues. In the inefficacy group, 13/27 patients (48%) responded to eltrombopag, and 11/22 patients (50%) responded to rh-TPO. In the non-efficacy-related group, 22/26 patients (85%) and 15/21 patients (71%) in the eltrombopag and rh-TPO groups maintained their response rates at 6 months after switching, respectively. Both eltrombopag and rh-TPO were well tolerated. Conclusions: Our study confirmed the safety and effectiveness of switching between rh-TPO and eltrombopag for ITP patients who had no response to or experienced adverse events with their first TPO-RA. When the switch was motivated by other reasons, including patient preference and platelet count fluctuations, the probability of response was high. Registration: ClinicalTrials.gov, NCT04214951.